The Panoptica of the Ambrosian Library as an Example of Synergy of Modern Ideas - Henczel, Ligia (Sensus Historiae, 2025)
The Ambrosian Library is one of the oldest cultural institutions in Milan, founded by Cardinal Frederick Borromeo at the beginning of the 17th century. Its integral part is the Pinacotheca. The founder’s idea was to create a scientific and artistic institution and make it available to anyone who “can read and write.” To this end, he donated tens of thousands of books and manuscripts, a collection of works of art and many exhibits, the so-called curiosities, to the library. Currently, the collection of Veneranda Biblioteca Ambrosiana includes over a million prints, thousands of incunabula and manuscripts, with the world’s largest collection of Leonardo da Vinci’s drawings, canvases by famous masters, sculptures, astronomical instruments, tombstone reliefs, busts, utility objects, ancient maps, numismatic items, shells, stained glass windows, and even Polonica. Due to the value of the collection, it is one of the most valuable Italian and world institutions of this type.